Assessment of Physicochemical Parameters and Phytoplankton of Eme River, Umuahia, Southeast Nigeria - Emeka Donald Anyanwu; Onyinyechi Gladys Adetunji; Solomon Nnanna Umeham (Program Pascasarjana Universitas Sriwijaya, 2021)
Aquatic ecosystems respond differently to diverse anthropogenic activities in their watersheds. Phytoplankton is sensitive to their environment and is used to monitor anthropogenic impacts. A study was carried out in a South-eastern Nigerian River between December 2017 and November 2018 in 6 stations; to assess the phytoplankton community, water quality, and anthropogenic impacts. Sand mining was a major activity in the river among others. The phytoplankton was sampled with the filtration method while water was collected and analyzed using standard methods. A total of 36 phytoplankton species were recorded with Chlorophyceae being the most abundant group. The most abundant species - Melosira granulata is a pollution indicator. The water quality and phytoplankton structure showed that the water was tending towards eutrophication. This is attributed to the observed anthropogenic activities and cumulative impacts of all the activities in the watershed. The impact of sand mining activities was observed more in the downstream stations (4 – 6) while perturbation from swimming children and related activities was observed in station 1. The community structure reflected the impacts of the activities while CCA showed the major water quality parameters that influenced the phytoplankton community structure.